4-Hydroxytamoxifen induces slight uncoupling of mitochondrial oxidative phosphorylation system in relation to the deleterious effects of tamoxifen - Cardoso, Carla M. P. (2002)
The use of tamoxifen (TAM) has been questioned on the chemotherapy and chemoprevention of breast cancer due to several estrogen receptor-independent cytotoxic effects. As an alternative, its more active metabolite 4-hydroxytamoxifen (OHTAM) has been proposed with presumed lower side effects. In this work, the potential OHTAM toxicity on rat liver mitochondrial bioenergetics in relation to the multiple deleterious effects of TAM was evaluated. OHTAM, at concentrations lower than those putatively reached in tissues following the administration of TAM, does not induce significant perturbations on the respiratory control ratio (RCR), ADP/O, transmembrane potential ([Delta][Psi]), phosphorylative capacity and membrane integrity of mitochondria. However, at high concentrations, OHTAM depresses the [Delta][Psi], RCR and ADP/O, affecting the phosphorylation efficiency, as also inferred from the [Delta][Psi] fluctuations and pH changes associated with ADP phosphorylation. Moreover, OHTAM, at concentrations that stimulate the rate of state 4 respiration in parallel to the decrease in the [Delta][Psi] and phosphorylation rate, causes mitochondrial swelling and stimulates both ATPase and citrate synthase activities. However, the OHTAM-observed effects, at high concentrations, are not significant relatively to the damaging effects promoted by TAM and suggest alterations to mitochondrial functions due to proton leak across the mitochondrial inner membrane.